Answer:
-1/6
Step-by-step explanation:
5a+2/3=-1/6
5a=-1/6-2/3
5a=-1/6-4/6
5a=-5/6
a=(-5/6)/5
a=(-5/6)(1/5)
a=-5/30
simplify
a=-1/6
Answer:
Sorry but we need more info.
Step-by-step explanation:
:)
Answer:
19
Step-by-step explanation:
5x8 is 40
59-40 is 19
Answer:
y = 5^x
Step-by-step explanation:
y= b*(a)^x + c
c could = 1 but then you would not have an exponential function. c = 0 because the graph follows the x axis up until x = -2. Suppose c = 1. The the graph would follow y = 1 up until x = - 2
When x = 0, y = 1 which means that b. If b is anything but 0 or 1 then the y intercept would be stretched to a different place. If be = 0 then y would = 0.
So the graph is of the form y = a^x
Now when x = 0 the graph, the y intercept is y = a^0 or y = 1 So the y intercept is (0,1)
Now the next point is thing to solve for is a.
When x = 1, y = 5 (read the graph)
y = a^x
5 = a^1
5 = a because a^1 is a.
Answer
y = 5^x.
5 = a^1
The first box is 3 more than the quotient of 6 and a number, the second is 6 less than the product of 3 and a number, the third box is the product of 6 and the sum of a number and 3.